BRCA Variants Do Not Increase the Risk of Adverse Reactions in Patients With Ovarian Cancer: A Single-Center Real-World Study - Li, Kemin; Zeng, Jing; Zhang, Mengpei; Yin, Rutie; Li, Zhengyu (Frontiers in Oncology, 2022)
Objective: To study the correlation between BRCA mutation status and the risk of adverse reactions in patients with ovarian cancer. Method: A real-world study was conducted at the largest gynecological oncology center in western China, the West China Second University Hospital of Sichuan University. The research subjects were patients diagnosed with ovarian cancer who were initially treated in our hospital from January 2016 to January 2020 and had their BRCA gene status evaluated. Multivariate Cox analysis was conducted to investigate the correlation between the BRCA mutation status and adverse reactions in ovarian cancer patients during initial treatment. Results: A total of 349 ovarian cancer patients were enrolled, including 79 patients with pathogenic BRCA variants, resulting in a pathogenic mutation rate of 22.6%. Among these 79 patients, 57 had BRCA1 variants and 22 had BRCA2 variants, yielding a pathogenic mutation rate of 16.3% and 6.3%, respectively. Multivariate COX analysis revealed that pathogenic BRCA variants were not related to the risk of adverse reactions, such as myelosuppression and allergies to chemotherapy drugs, during the initial treatment of ovarian cancer. Conclusion: BRCA variants did not increase the risk of adverse reactions, such as myelosuppression and allergies to chemotherapy drugs, in ovarian cancer patients during initial treatment.